2016
DOI: 10.1080/13102818.2015.1126201
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of culture conditions to improve the expression level of beta1–epsilon toxin ofClostridium perfringenstype B inEscherichia coli

Abstract: The detoxified beta1Àepsilon (b1Àe) toxin protein of Clostridium perfringens type B provides protection from C. perfringens types B, C and D infections. Acetate is the primary by-product from the cell growth and expression of b1Àe protein. In the present study, the effects of pH and dissolved oxygen (DO) on the expression of b1-e protein were investigated. Two-stage pH and DO control strategies were developed for the expression of b1Àe protein. The obtained results indicated that higher cell density and concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…The accumulation of acetate in culture media has a negative impact on strain productivity, since this organic acid is toxic for E. coli and it also represents the loss of the important metabolic precursor AcCoA [5, 6]. Strategies to eliminate or mitigate overflow metabolism include the use of glucose feeding strategies to limit the concentration of this sugar in culture media, as well as the generation of mutant strains with defective acetate-production pathways or reduced glucose import capacity [79]. The reduction of glucose import capacity by the inactivation of genes encoding glucose transporters has been proven a successful strategy for improving E. coli strains for the production of recombinant proteins, DNA vaccines and chemicals [1012].…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of acetate in culture media has a negative impact on strain productivity, since this organic acid is toxic for E. coli and it also represents the loss of the important metabolic precursor AcCoA [5, 6]. Strategies to eliminate or mitigate overflow metabolism include the use of glucose feeding strategies to limit the concentration of this sugar in culture media, as well as the generation of mutant strains with defective acetate-production pathways or reduced glucose import capacity [79]. The reduction of glucose import capacity by the inactivation of genes encoding glucose transporters has been proven a successful strategy for improving E. coli strains for the production of recombinant proteins, DNA vaccines and chemicals [1012].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, for E. coli , it was reported that the pH values of less than 6.0 would negatively affect the cell growth 52 , 53 . Therefore, for in vivo esterification, it was necessary to select an optimal pH at which the enzyme activity would be relatively high and at the same time without negatively affecting the cell growth 54 . Hence, a separate set of in vitro study was performed for pH optimization.…”
Section: Discussionmentioning
confidence: 99%
“…Another successful approach is based on genetic modifications that eliminate acetate synthesis pathways or reduce glucose import capacity by deleting genes that encode transporter proteins. These strategies have been proven to be successful in increasing the production of chemicals, plasmid DNA vaccines, and recombinant proteins [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%